Analisis Penggunaan Dan Kelengkapan Informed Consent Pada Tindakan Sectio Caesarea Di Rumah Sakit PKU Muhammadiyah Surakarta Tahun 2017 - Bekti Suharto - Poltekkes Bhakti Mulia (Indonesian Journal on Medical Science, 2018)
Abstract : The results of a preliminary study of 15 DRM unknown completeness informed consent 66.7% identity, the identity of the approval of 66.7%, and the highest lack of accessories on the signature of the witness II 80%. the use of anesthesia status of 93.4%, the completeness of identity of 60%, and highest in non accessory doctor's signature and the signatures of witnesses 66.7%. This shows the use of informed consent and charging status along with high relatife anesthesia, causing the value legalitat be less. To identify the use of informed consent to the act sectio caesarea in PKU Muhammadiyah Hospital in Solo in 2017. Observation and interview, descriptive study, a retrospective approach. The object of research DRM sectio caesarea 2015 population of 960 samples taken 282 DRM. Of the 282 DRM sectio caesarea use of informed consent informed consent are 97.51%, 75.17% idntitas completeness, comprehensiveness identity 53.19% approval, and the highest percentage outentifikasi the signatures of witnesses II 34.39%. The use of anesthesia status 88.65%, completeness of identity as much as 69.85%, and the highest percentage outentifikasi on the signature of a witness - a witness 36.17%. The cause of the lack of medical personnel carefully situations, which scattered form or proficiency patients understand and fill out the form. The use and charging Informed consent is already well along anesthesia status it needs to be improved so that aspect of the legality of medical services and high quality.Keywords: informed consent, sectio caesarea, status of anesthesia. Abstrak : Data awal penulis mendapatkan sejumlah 15 DRM diketahui kelengkapan pengisian identitas informed consent 66,7%, identitas persetujuan 66,7%, dan ketidak lengkapan tertinggi pada  tanda tanggan saksi II 80%. penggunaan status anestesia 93,4%, kelengkapan identitas 60%, dan ketidak lengkapan tertinggi pada tanda tangan dokter dan tanda tangan saksi-saksi 66,7%. Hal ini menunjukan penggunaan dan pengisian informed consent berserta status anestesia relatife tinggi, menyebabkan nilai legalitat menjadi kurang. Mengetahui penggunaan informed consent pada tindakan sectio caesarea  Rumah Sakit PKU Muhammadiyah Surakarta  yang telah lulus akreditasi paripurna type B Observasi dan wawancara, jenis penelitian deskriptif, pendekatan retrospektif. Objek penelitian DRM sectio caesarea tahun 2017 populasi 960 RM sample yang diambil 282. Dari 282 DRM sectio caesarea penggunaan informed consent 97,51% terdapat informed consent, kelengkapan pengisian idntitas 75,17%, kelengkapan identitas persetujuan 53,19%, dan prosentase outentifikasi tertinggi pada tanda tangan saksi II 34,39%. Penggunaan status anestesia 88,65%, kelengkapan pengisian identitas sebanyak 69,85%, dan presentase outentifikasi tertinggi pada tanda tangan saksi - saksi 36,17%. Penyebab ketidak telitian dari petugas medis, formulir yang tercecer atau kecakapan pasien memahami dan mengisi formulir. Penggunaan dan pengisian Informed consent berserta status anestesia sudah baik maka perlu di tingkatkan agar  pelayanan medis dan legalitas bermutu tinggi.Kata Kunci: informed consent, sectio caesarea, status anestesia.